Making Corporate Reports Valuable: A Survey of Corporate Reporting Practices by Major U.K. Companies. - Usry, Milton F.; Moriarity, Shane R. (The Accounting Review, 1992)
Reviews the book `The Costing Heritage: Studies in Honor of S. Paul Garner,' by O. Finley Graves.